DBI-DeLP: a framework for defeasible argumentation over databases - Deagustini, Cristhian A. D. (2011)
Nowadays Argumentation Systems in general, and DeLP in particular, build arguments based on the context of a single and xed logical program. This leads to a practical limitation regarding the volume of data in which the argumentation is supported, because integration of constantly updated external data only can be made by the "hard-coding" of facts (i.e., the explicit codi cation of facts in the program), which is inne cient for massive data. This paper introduces Database Integration for Defeasible Logic Programming (DBI-DeLP), a framework that integrates Defeasible Argumentation with Databases that may be updated by other external applications, allowing the execution of argumentation processes based on masive external sources of data.